Die Zinsstruktur als Indikator der Geldpolitik? - Helmut Hesse; Gisela Roth (Kredit und Kapital, 1992)
Die Zinsstruktur als Indikator der Geldpolitik? Der vorliegende Beitrag geht der Frage nach, ob die Zinsstruktur als Indikator der deutschen Geldpolitik geeignet ist. In den Vereinigten Staaten wird seit geraumer Zeit darüber diskutiert, ob die Zinsstruktur der durch Finanzinnovationen in ihrer Informationsfunktion beeinträchtigten Geldmenge vorzuziehen sei. Empirische Untersuchungen aus den Federal Reserve Banks über den Zusammenhang zwischen der Zinsstruktur und dem realen Bruttosozialprodukt sowie dem Preisniveau kommen für die Vereinigten Staaten zu dem Ergebnis, daß die Zinsstruktur erheblichen Erklärungswert für die zukünftigen Bewegungen beider Endziele der Wirtschaftspolitik aufweist. Drei dogmengeschichtliche Entwicklungslinien können zur theoretischen Fundierung eines Zinsstrukturindikators herangezogen werden: die Relation Q von James Tobin, die Erwartungstheorie der Zinsstruktur von Irving Fisher und die Zinstheorie von Knut Wicksell. Letzterer kann als der eigentliche Begründer des indikatortheoretischen Zinsstrukturansatzes gelten, weil auf ihn die Vorstellung zurückgeht, daß die Geldpolitik über ihren Einfluß auf das Verhältnis zweier Zinssätze zueinander wirksam wird. Im Rahmen der theoretischen Überprüfung eines Zinsstrukturindikators wird die Hypothese aufgestellt, daß er weniger innovationsanfällig ist als Geldmengenaggregate. Diese – noch abzusichernde Hypothese – spricht für die Verwendung eines Zinsstrukturindikators; dagegen spricht vor allem die Einschränkung seiner Aussagekraft durch internationale Kapitalbewegungen. Der empirische Zusammenhang zwischen der Zinsstruktur und dem Bruttosozialprodukt ist in Deutschland sehr eng; Zinsstruktur und Preisniveau weisen einen weniger engen Zusammenhang auf. Als Ergebnis der Analyse bleibt festzuhalten, daß die Zinsstruktur nicht als Indikator der deutschen Geldpolitik geeignet ist. In einer durch hohe Auslandsabhängigkeit gekennzeichneten Volkswirtschaft wiegt die Beeinträchtigung der Informationsfunktion der Zinsstruktur durch internationale Kapitalbewegungen schwer. – – The Interest Rate Structure as a Monetary Policy Indicator This contribution analyzes whether the interest rate structure would be a suitable monetary policy indicator in Germany. A discussion has been going on in the United States for some time on whether the interest rate structure should, as an indicator, be preferred to money supply whose informatory value has been impaired by financial innovations. Empirical studies by the Federal Reserve Bank of the interrelationships between the interest rate structure and the Gross National Product in real terms as well as the level of prices have reached the conclusion for the United States of America that the interest rate structure is of great informatory value for future movements of both final goals of economic policy. There are three trends in economic theory that serve as the theoretical foundations ofanindicator that is based on the interest rate structure: The relation Q according to James Tobin, the theory of expectations for the interest rate structure according to Irving Fisher and the interest rate theory according to Knut Wicksell. The latter must be deemed to have been the real inventor of the theory that the interest rate structure can be used as an indicator, because it was he who fathered the opinion that monetary policy is effective through its influence on the ratio between two interest rates. Within the framework of a theoretical review of an indicator based on the interest rate structure, the hypothesis is made that this indicator is less prone to innovation than the money supply aggregates. This hypothesis, which must still be substantiated in academic terms, speaks in favour of the indicator based on the interest rate structure; the correctness of this view is doubtful mainly because its meaningfulness is limited by international capital movements. The empirical interrelationship between the interest rate structure and the Gross National Product is very close in the German case; the interrelationship between the interest rate structure and the level of prices is less close, however. The conclusion to be reached from this analysis is that the interest rate structure is no suitable indicator for German monetary policy. Inan economy whose main characteristic is strong international economic dependence, the limitation of the informatory function of the interest rate structure on account of international capital movements may not be neglected.
Keywords: 330